2022
DOI: 10.3390/antibiotics11050669
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Interventions to Improve Antimicrobial Resistance Awareness and Behavioural Change Associated with Antimicrobial Use: A Systematic Review Exploring the Use of Social Media

Abstract: Introduction: Over the years there have been several interventions targeted at the public to increase their knowledge and awareness about Antimicrobial Resistance (AMR). In this work, we updated a previously published review by Price et al. (2018), on effectiveness of interventions to improve the public’s antimicrobial resistance awareness and behaviours associated with prudent use of antimicrobials to identify which interventions work best in influencing public behaviour. Methods: Five databases—Medline (OVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Interventions targeted at GP have shown successes and updates or adjustments to focus these campaigns in the light of our findings may be timely [ 27 , 28 , 29 ]. A recent review of public awareness campaigns on antibiotic prescribing and awareness highlighted that outcome measures to evaluate these campaigns differ widely, and no long-term outcomes (beyond 6 months) were included [ 30 ]. Additionally, it showed that social media was not used as a tool to increase public awareness, which may offer opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions targeted at GP have shown successes and updates or adjustments to focus these campaigns in the light of our findings may be timely [ 27 , 28 , 29 ]. A recent review of public awareness campaigns on antibiotic prescribing and awareness highlighted that outcome measures to evaluate these campaigns differ widely, and no long-term outcomes (beyond 6 months) were included [ 30 ]. Additionally, it showed that social media was not used as a tool to increase public awareness, which may offer opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the majority of similar studies have reported pediatricians as the preferred source of information, such as studies conducted in Cyprus [ 19 ] and Palestine [ 34 ], a study in China conducted by Xiang et al [ 35 ] identified television as the main source of information regarding the use or misuse of antibiotics. Studies have shown that education about the rational use of antibiotics is useful in increasing knowledge, but that they have very little effect in changing the attitudes and practices of the public towards the use of antibiotics [ 36 , 37 ]. Different types of interventions aimed at the rational use of antibiotics (educational interventions, theatrical and musical interventions, gamification, animated film, fear-based messages highlighting the side effects of antibiotic use, digital interventions), which until now have been used in the world and mostly target the public, have produced modest results [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that education about the rational use of antibiotics is useful in increasing knowledge, but that they have very little effect in changing the attitudes and practices of the public towards the use of antibiotics [ 36 , 37 ]. Different types of interventions aimed at the rational use of antibiotics (educational interventions, theatrical and musical interventions, gamification, animated film, fear-based messages highlighting the side effects of antibiotic use, digital interventions), which until now have been used in the world and mostly target the public, have produced modest results [ 36 ]. A study examining the impact of a television campaign on antibiotic use indicated that it was wrong to emphasize that the antibiotic user was responsible for the development of resistance because it was interpreted as childish by viewers.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there is a need for deeper and more extensive social outreach to actively disseminate health information, for example on appropriate antibiotic use and AMR, to these sub-populations, as they are less likely to present themselves to a healthcare facility or have interest to actively seek out health information. Contemporary communication channels such as social media posts by trusted healthcare providers, with interactive games and videos embedded could be considered to provide health information to this sub-population with LL-HIO [ 35 ].…”
Section: Discussionmentioning
confidence: 99%